Public health significance of immunization and epidemic occurrence of measles - Lejla Čalkić; Muhamed Skomorac; Salih Tandir; Suad Sivić; Lejla Bajramović-Omeragić (Medicinski glasnik, 2017)
Aim: To investigate epidemiological characteristics of the measles epidemic (risk factors and reasons for its emergence) in order to establish better control and prevention of future epidemics as well as to determine an influence of poor collective immunization of children against measles on appearance of epidemic disease. Methods: An open retrospective epidemiological study of measles infection was conducted during the epidemic in Zenica-Doboj Canton (ZDC) in the period 2014-2015. Disease reports, Disease Reporting Forms for measles and rubella cases and the Bulletin of the Institute for Health and Food Safety Zenica were used for data collection. Results: A total of 325 patients with the diagnosis of measles were registered, 262 (80.61%) in 2014 and 63 (19.39%) in 2015 resulting in overall incidence of 81.25/100.000. The majority of patients were aged 0-6 (p <0.05). Of the total number of patients, only 13 (4.73%) were orderly vaccinated (p <0.05). In the period 2009-2015 in ZDC 25.444 (83.34%) children (p <0.05) were vaccinated with measles, mumps, rubella (MMR) vaccine. Conclusion: Results: of the study show that the low level of vaccination of children continues to a risk of the emergence of epidemics of measles and other infectious diseases. Therefore, in order to prevent the disease there is a need for a better vaccination campaign.
Keywords: measles; children; vaccination; Bosnia and Herzegovina